Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

Instantané de recherche : portrait de la santé mentale des Canadiens francophones en situation minoritaire - CAMH-Evidence Exchange Network (2020)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Le difficile pilotage d’une réforme d’un système de santé : le cas du Nouveau-Brunswick (Canada) - Collin, Stéphanie; Lamothe, Lise (Santé publique, 2020)

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

Les Canadiens partiellement français sont susceptibles à une augmentation des facteurs de risque cardiovasculaire : une étude de cohorte rétrospective basée sur la population - Daccache, J.; Savoury, M.; Yam, Y.; Chow, B. J. M. (Annales de Cardiologie et d'Angéiologie, 2020)
Introduction Grâce à diverses recherches menées dans le passé, il a été démontré que le Québec est la province avec les taux d’infarctus aigü du myocarde (IAM) et la prévalence des facteurs de risque cardiovasculaire les plus élevés au Canada. Cette étude proposée effectuera une analyse rétrospective sur les populations caucasiennes, afin d’analyser les facteurs de risque cardiovasculaire dans les populations partiellement francophones par rapport aux Canadiens-Français et non-Français. En outre, nous analyserons de près les deux sexes des populations susmentionnées. Méthode Cette étude de cohorte rétrospective, basée sur la population, a été réalisée en utilisant le registre de l’ACTC de l’Institut de cardiologie de l’Université d’Ottawa (ICUO). Les participants sont des patients de race blanche de tout âge, qui sont venus à l’ICUO pour une angiographie par tomodensitométrie, entre 2006 et 2018, et qui ont donné leur consentement éclairé. SPSS a été utilisé pour comparer les différentes populations (Canadiens-Français [CF], Canadiens partiellement Français [CPF], et Canadiens non-Français [CNF]) et les différents sexes. Résultats La population des CPF ressemble plus à celle des FC, ayant une incidence plus élevée de facteurs de risque cardiovasculaire tels que le tabagisme, la dyslipidémie et le diabète de type 2. Interprétation Nos résultats suggèrent que les CPF, comme les CF, pourraient bénéficier d’une éducation plus intensive et de techniques de modification du mode de vie.

Mental health status and help-seeking strategies of international students in Canada - de Moissac, Danielle; Graham, Jan Marie; Prada, Kevin; Gueye, Ndeye Rokhaya; Rocque, Rhéa (Canadian Journal of Higher Education, 2020)
International students are at heightened risk of developing psychological distress, yet little research has been conducted on their mental health or support needs. This quantitative study focused on undergraduate students at two mid-sized universities in Manitoba, Canada. Online and paper surveys were completed by 932 participants, of whom 21% identified as international students. This paper, descriptive in nature, outlines the sociodemographic profiles, current mental health status, psychological characteristics, and coping strategies of international students compared to domestic students in each institution. Data show that international students are more likely to report excellent mental health, score higher on the mental health scale, and report higher life satisfaction, higher self-esteem, and more positive body image than domestic respondents. However, they are less likely to talk about their hardships. Providing culturally-adapted supports that take into consideration ethnolinguistic differences, religious practice, and mental health literacy will better meet the needs of international students on campus.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020 - Forest, Mariève (Consortium national de formation en santé - Volet Université d'Ottawa, 2020)
fs-ref-orig: Forest, M. (2020). Analyse des retombées des fonds de recherche du CNFS - Volet université d'Ottawa, période 2013-2020. Consortium national de formation en santé - Volet Université d'Ottawa. fs-code-orig: Forest-2020

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Utilisation de produits psychoactifs pour améliorer la performance intellectuelle ou physique en milieu postsecondaire - Gueye, Ndeye Rokhaya; de Moissac, Danielle; Kinkumba, Babou; Delaquis, Stéfan (Drogues, santé et société, 2020)
Introduction Substance use and impaired driving increase risk of motor vehicle crashes and deaths. Individual, socio-economic and -cultural factors are associated with these at-risk behaviors; however, little is known if differences exist between the Anglophone majority and minority Francophone populations in Canada. This article describes prevalence of substance use, impaired driving and driving practices by postsecondary student and compares Francophones and Anglophones with respect to these behaviors. Methods Postsecondary students between 18 and 24 years attending a Francophone university in Western Canada completed a paper-based survey during class-time. Results Prevalence of alcohol consumption, binge drinking and marijuana use in the past month were 88.6%, 64.2% and 22.7% respectively. Francophone participants were more likely to consume more alcohol, participate in drinking games, and consume marijuana during the past month than Anglophones. They were also more likely to report impaired-driving, speeding, distracted driving and being passenger in a motor vehicle driven by an impaired driver. Conclusion Awareness campaigns on campus highlighting the risks of substance use and unsafe driving practices should be strengthened and target Francophone students in linguistic minority communities.

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Les Effets Potentiels de la Version Française du NCLEX-RN® sur le Choix de la Langue de Formation d'Étudiantes Infirmières Francophones en Situation Minoritaire. - Lalonde, Michelle; Chartrand, Julie; Vanderspank- Wright, Brandi; McGillis Hall, Linda; Gosselin-Bélanger, Amélie; Fullum, Jessica Adèle (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
Background: Since the introduction of the new entry to practice exam, the NCLEX-RN®, there has been a very low success rate among Francophone nursing students living in minority situations. In addition, there has been a drop in the number of candidates who choose to write the exam in French. These results are of great concern in terms of the quality and sustainability of French language health services in French language minority communities in Canada. Objectives: The purpose of this article is to present the results of a study exploring the experiences of students enrolled in an entry level nursing program in French in terms of their decision-making regarding: 1) the choice of the language of the nursing program in which they were enrolled, 2) the language in which they chose to write the NCLEX-RN®, 3) their interest in working in a Francophone context, 4) their general knowledge of the new entry to practice exam, and 5) information sources on the NCLEX-RN©. Methodology: A sequential mixed methods design using surveys with multiple-choice and open-ended questions was used to conduct this study. Descriptive analyzes, as well thematic and content analysis, were used to analyze the data. Results: 51 students from a francophone graduating cohort participated in this study. The majority of the participants expected to write the NCLEX-RN® in English; the media attention on the French version of the exam influenced their decision. Four main themes were highlighted : 1) Choice of language of student based on their first language, 2) Three main factors that influence the choice of the language in which they write the NCLEX-RN®, 3) Colleagues and media as sources of information on the NCLEX-RN®, and 4) Importance and pride of studying in French. Conclusion: The results of this project shed light on the factors that influence francophone students' decision-making regarding the choice of language for the exam and the reasons why graduating students would choose to study in French again or not. , Contexte : Un très faible taux de réussite a été remarqué chez les étudiantes infirmières francophones en situation minoritaire ainsi qu’une chute du nombre de candidates qui choisissent de passer en français le nouvel examen d’autorisation, le NCLEX-RN®, qui a été introduit en 2015. Ces données sont préoccupantes s’agissant de la qualité et de la pérennité des services de santé en français dans les régions linguistiques minoritaires au Canada. Objectifs : Le but de cet article est de présenter les résultats concernant les expériences des étudiantes inscrites dans un programme de formation initiale en sciences infirmières en français sur leur prise de décision quant à : 1) la langue du programme auquel elles se sont inscrites, 2) la langue dans laquelle elles ont choisi de passer le NCLEX-RN®, 3) leur intérêt à travailler dans un contexte francophone, 4) leurs connaissances générales relatives au nouvel examen d’autorisation et 5) les sources d’information sur le NCLEX-RN®. Méthodologie : Un devis de recherche mixte séquentiel a été retenu comportant l’utilisation de questionnaires. Des analyses descriptives et des analyses thématiques et de contenu ont été effectuées. Résultats : 51 étudiantes de la cohorte francophone ont participé à cette étude. La majorité des participantes comptaient passer le NCLEX-RN® en anglais; l’intérêt médiatique porté à la version française de l’examen a eu une influence sur leur décision. Quatre grands thèmes ont été mis en évidence à partir des questions à court développement du questionnaire : 1) langue maternelle choisie comme langue de formation, 2) trois principaux facteurs qui influencent le choix de la langue pour le NCLEX-RN®, 3) collègues et médias comme sources d’information sur le NCLEX-RN®, et 4) importance et fierté d'étudier en français. Conclusion : Les résultats de ce projet ont mis en évidence les facteurs qui influencent la prise de décision des étudiants francophones quant au choix de la langue de l’examen et les raisons pour lesquelles les finissantes étudieraient à nouveau en français.

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

The revised patient perception of patient-centeredness questionnaire: Exploring the factor structure in French-speaking patients with multimorbidity - Nguyen, Tu Ngoc; Ngangue, Patrice Alain; Ryan, Bridget. L.; Stewart, Moira; Brown, Judith. B.; Bouhali, Tarek; Fortin, Martin (Health Expectations, 2020)
Background The Patient Perception of Patient-Centeredness (PPPC) questionnaire was revised, and there is a need for the questionnaire to be tested in diverse primary care populations. Objectives This study aimed to examine the factor structure of the Revised PPPC questionnaire (PPPC-R) in French-speaking patients with multimorbidity. Design Secondary analysis from baseline data of the French arm of Patient-Centered Innovations for Persons with Multimorbidity Study (PACEinMM Study). Setting and participants Participants were adult patients with multimorbidity attending primary health-care settings. Outcome measures Exploratory factor analyses were applied to examine the factor structure of the PPPC-R. Cronbach's alpha values were calculated to assess the internal consistency of the whole questionnaire and of each factor explored. Results There were 301 participants, mean age 61.0, 53.2% female. The PPPC-R showed very good internal consistency, with three factors: Patient-Centered Clinical Method (PCCM) Component 1-Exploring the health, disease and illness experience + PCCM Component 4-Enhancing the patient–clinician relationship (Factor 1); PCCM Component 2-Understanding the whole person (Factor 2); and PCCM Component 3-Finding common ground (Factor 3). There was a good internal consistency within each factor (Cronbach's α = 0.87 for 8 items in Factor 1, 0.77 for 5 items in Factor 2 and 0.87 for 5 items in Factor 3). Discussion and conclusions The French PPPC-R factor structure was in accordance with the underpinning conceptual model and presented with three factors. Further assessment of its validity and reproducibility are needed to allow its use as a measure of patient's perception of patient-centeredness.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p < 0.001) and Francophones (6.15%, p < 0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p < 0.001 and RR = 1.41, p < 0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)
fs-ref-orig: Réseau des services de santé en français de l’Est de l’Ontario. (2020). Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire. fs-code-orig: Réseau des services de santé en français de l’Est de l’Ontario-2020

Rapport provincial sur les SSEF (données de 2018-2019) - Réseau des services de santé en français de l'Est de l'Ontario; Institut Ozi (2020)
Le projet OZi a pour objectif de colliger et d’analyser des données afin de dresser un portrait de la capacité de SSEF. Cette initiative cherche à pallier le manque de données normalisées afin de permettre une planification efficace et une prise des décisions éclairée. Grâce au portail OZi, les fournisseurs de services de santé (FSS) financés par les RLISS ont fourni des données de référence sur leur capacité en matière de SSEF. Le présent rapport porte sur la deuxième année de collecte de données (année 2018-2019). L’analyse porte sur quatre perspectives : la répartition des FSS, le continuum des services, la conformité en matière de désignation et les ressources humaines.

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Centre de recherche en santé dans les milieux ruraux et du nord. fs-code-orig: Sanou-2020b

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)
fs-ref-orig: Sanou, B., Gauthier, A. P., Hien, A., Michel, I. et Timony, P. (2020). Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique. Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal. fs-code-orig: Sanou-2020c

Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Inégalités sociales et enjeux liés à la santé des aînés francophones en situation minoritaire : le cas de l’Atlantique et de l’Acadie des Maritimes - Simard, Majella; Bouchard, Louise (Organisations & Territoires, 2020)
Le vieillissement démographique soulève des enjeux fondamentaux dans la réponse des acteurs sociaux aux besoins manifestés par les aînés sur le plan de la santé. L’objectif de cette contribution est double. Il consiste, d’une part, à identifier les principaux enjeux auxquels sont confrontés les aînés francophones en situation minoritaire sur le plan de la santé et, d’autre part, à examiner la situation des inégalités sociales et les conditions de vie qui en découlent comme déterminant de la santé, de la qualité et de l’accès aux services dans une perspective de développement territorial. Les résultats de notre analyse révèlent que le rapport minoritaire/ majoritaire traduit une inégalité sociale qui, couplée à d’autres déterminants sociaux, contribue de facto à la formation de disparités sur le plan de la santé, d’où la nécessité de mettre en oeuvre une politique à l’endroit des aînés vivant en milieu minoritaire francophone destinée à réduire de tels écarts.

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.